2013
DOI: 10.1186/2192-1709-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification from nitrogen-fixing biologically crusted soils in a cool desert environment, southeast Utah, USA

Abstract: Introduction: Nitrogen fixation by microorganisms within biological soil crust ("biocrust") communities provides an important pathway for N inputs in cool desert environments where soil nutrients are low and symbiotic N-fixing plants may be rare. Estimates of N fixation in biocrusts often greatly exceed that of N accretion rates leading to uncertainty regarding N loss pathways. Methods: In this study we examined nitrogen fixation and denitrification rates in biocrust communities that differed in N fixation pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 40 publications
1
51
0
Order By: Relevance
“…Barger et al (2013) report a relationship between nitrogen fixation and N 2 O release in biological soil crusts, which include lichens and bryophytes, as well as soil bacteria and algae. For this approach, however, reliable nitrogen fixation data are sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Barger et al (2013) report a relationship between nitrogen fixation and N 2 O release in biological soil crusts, which include lichens and bryophytes, as well as soil bacteria and algae. For this approach, however, reliable nitrogen fixation data are sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of N 2 O emissions by lichens and bryophytes, too, show considerable variation. Regarding biological soil crusts, several studies analysed denitrification rates to be negligible (Johnson et al, 2007;Strauss et al, 2012), and N 2 O production was calculated to constitute only 3-4 % of the N fixation rate (Barger et al, 2013). Other studies, however, described high denitrification rates that either increased (Brankatschk et al, 2013) or decreased with advancing crust development (Abed et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Low correlations were found between HONO or NO emissions and NH + 4 contents (R 2 = 0.165 and 0.232; p = 0.05). Thus, in the present study it seems that reactive nitrogen emissions predominantly depend on NO − 2 and NO − 3 contents and not on surface cover types, although biocrusts (especially with cyanobacteria and cyanolichens) are able to fix atmospheric nitrogen (Belnap, 2002;Elbert et al, 2012;Barger et al, 2013;Patova et al, 2016). The results of a two-factorial ANOVA showed that HONO or NO emissions were not significantly related to soil cover type but rather to nitrite content, i.e., its direct aqueous precursor.…”
Section: No and Hono Flux Measurementsmentioning
confidence: 99%
“…Globally it has been estimated that 100-290 Tg (N) yr −1 is fixed biologically (Cleveland et al, 1999), of which 49 Tg yr −1 (17-49 %) is fixed by cryptogamic covers, which comprise biocrusts, but also other microbially dominated biomes, like lichen and bryophyte communities occurring on soil, rocks and plants in boreal and tropical regions (Elbert et al, 2012). Studies have suggested that nitrogen cycling in soil (N 2 fixation, nitrification, denitrification) and hence reactive nitrogen emission (NO, N 2 O, HONO) is often enhanced by well-established biocrusts, especially by dark cyanobacteria (Cleveland et al, 1999;Elbert et al, 2012;Belnap, 2002;Barger et al, 2013;Johnson et al, 2005;Abed et al, 2013;Strauss et al, 2012;Weber et al, 2015). However, much of the molecular biology and chemistry that is important for atmosphere-land interactions likely occurs just below the crust (that is visible at the surface).…”
Section: Introductionmentioning
confidence: 99%
“…But what are the consequences of nitrogen fixation by biocrusts? Incubation studies have shown that biocrusts can release nitrogen oxides (20)(21)(22), while field and model studies suggested large emissions of nitrogen oxides from drylands, raising questions about their origin (9,11,23,24).…”
mentioning
confidence: 99%